Longitudinal exploration of the delivery of care following a successful antenatal practice change intervention - Hall, Alix; Doherty, Emma; Nathan, Nicole; Wiggers, John; Attia, John; Tully, Belinda; Elliott, Elizabeth J.; Oldmeadow, Christopher; Chiu, Simon; Kingsland, Melanie (Frontiers in Medicine, 2025)
IntroductionThis is a secondary analysis of a stepped-wedge trial. The sustainment of evidence-based care is essential for ongoing population benefits. In a randomized stepped-wedge controlled trial of public maternity services across three health sectors in New South Wales, Australia, we demonstrated a positive practice change related to addressing alcohol use during pregnancy. This change followed a 7-month implementation strategy conducted between February 2018 and November 2019. However, evidence suggests that the impact of implementation strategies may reduce over time. It is important to document when and if recommended care reduces, so that timely support for sustainment can be provided.MethodsAs a secondary analysis, an interrupted time series analysis of outcomes from the largest sector of the randomized stepped-wedge controlled trial was conducted. The analysis explored the rate, time points, and extent of change in women’s reported receipt of recommended antenatal care for alcohol consumption, following delivery of an effective implementation strategy.ResultsA total of 4,909 (82% consented) women were surveyed. The proportion of pregnant women receiving recommended care reduced significantly per week following the withdrawal of implementation support, for three of the four outcomes: assessment of alcohol consumption (% change per week: −0.66, 95% CI: −1.1, −0.26); advice not to consume alcohol during pregnancy and of potential risks (% change per week: −0.63, 95% CI: −1.1, −0.22); and complete care relevant to alcohol risk level (advice and referral) (% change per week: −0.64, 95% CI: −1.1,-0.22). Similar results were observed regardless of the timing of antenatal visits. A more rapid decline occurred for most outcomes from the end of implementation until approximately 30 weeks post-implementation.DiscussionDespite a reduction in the receipt of recommended care, rates were still higher post-implementation than pre-implementation. Receipt of recommended antenatal care for alcohol consumption declined after active implementation support was withdrawn. The findings suggest the need for ongoing monitoring of care delivery and the introduction of additional sustainability strategies at key time points post-withdrawal of implementation support.